Financial projection of the basic pension under selective eligibility criteria - Dohun Kim (KDI Journal of Economic Policy, 2024)
This study conducts a financial projection of the basic pension in Korea, which provides cash assistance to the bottom 70% of elderly individuals aged 65 and over. The projection is carried out under both expansion and selective eligibility criteria, with particular emphasis on the latter. Specifically, the study examines two well-discussed selective eligibility criteria: 1) fixing the eligibility threshold at the 2024 value and adjusting it according to the inflation rate, and 2) linking the eligibility threshold to the median household income figure. To estimate the number of recipients under these selective scenarios, the study projects the future income evolution of the elderly, assuming the continuation of past income trends. Using the financial model of the basic pension developed by Shin and Kim (2021), the study finds that total fiscal spending could be reduced by 22% under the first selective scenario and by 17% under the second selective scenario, relative to the current system, in real terms between 2024 and 2070. With these fiscal savings, the study concludes that the full benefit amount could be increased from the current level of 334,810 won to 435,000 won under the first scenario and to 405,000 won under the second scenario by 2025.
Keywords: H53; H55; I31; J10; 330; Basic Pension; Selective Eligibility Criteria; Pension Reform; Elderly Poverty; Financial Model of Basic Pension